PERBANDINGAN DRAINING METHOD DENGAN SPITTING METHOD TERHADAP VOLUME SALIVA MAHASISWA FAKULTAS KEDOKTERAN GIGI UNIVERSITAS ANDALAS ANGKATAN 2011 DENGAN STIMULASI AROMA MAKANAN - Friska Meininda Putri; Nila Kasuma; Mery Ramadani (Faculty of Dentistry Universitas Andalas, 2015)
Saliva has been used in diagnostic procedures. Draining method and spitting method are a saliva collection method that is often used for diagnostic and therapeutic purposes based saliva. The purpose of this research is to determine comparison of draining method and spitting method to saliva volume students of Dentistry Faculty Andalas University class of 2011 with aroma of food stimulation. This observational research with cross sectional study approach has been held to 17 students of Dentistry Faculty in Andalas University class of 2011 that ages are 20-21 years old that is matched with the inclusion criteria. The volume of saliva collected is expressed in unit of ml. Univariate data analysis is carried out to describe each variables, to see normal distribution (p > 0,05) Shapiro Wilk normality test is performed. After distribution is proven to be normal, dependent T-test is performed to determine the mean differences between the draining method and the spitting method. Based on dependent T-test, average saliva volume students of Dentistry Faculty in Andalas University class of 2011 with the draining method is x ± SD = 2,5 ± 1,11 ml and the volume of saliva by spitting method is x ± SD = 3,72 ± 1,84 ml and p value < 0,05. Based on the research finding, it can be concluded that there are significant differences in the average saliva volume in the spitting method is higher than the draining method.